PENGARUH AUDIT TENURE DAN TEKANAN KLIEN TERHADAP INDEPENDENSI AUDITOR DENGAN KOMITMEN PROFESIONAL SEBAGAI VARIABEL MODERASI - Nur Afnitasary Nasir; Andi Wawo; Puspita Hardianti Anwar (Universitas Islam Negeri Alauddin Makassar, 2021)
This research is intended to determine the effect of tenure audits and client pressure on auditor independence. In addition, this study also wants to know how to influence professional commitment as a moderation of the relationship between tenure audit and client pressure on the independence of auditors in KAP in makassar and Gowa. This research is a quantitaf study using a descriptive approach of the population in this study is the Public Accounting Firm in Kab. Gowa and Makassar. The sample in this study is an Auditor who works in KAP Gowa and Makassar. The data analysis techniques in this study are multiple regression and regression analysis moderation with interaction approaches. The results of the hypothesis in this study showed that audit tenure had a significant positive effect on the auditor's independence and client pressure had a significant negative effect on the auditor's independence.